2018
DOI: 10.3390/en11061573
|View full text |Cite
|
Sign up to set email alerts
|

Boron Monochalcogenides; Stable and Strong Two-Dimensional Wide Band-Gap Semiconductors

Abstract: In this short communication, we conducted first-principles calculations to explore the stability of boron monochalcogenides (BX, X = S, Se or Te), as a new class of two-dimensional (2D) materials. We predicted BX monolayers with two different atomic stacking sequences of ABBA and ABBC, referred in this work to 2H and 1T, respectively. Analysis of phonon dispersions confirm the dynamical stability of BX nanosheets with both 2H and 1T atomic lattices. Ab initio molecular dynamics simulations reveal the outstandi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…From our calculations, it is observed that our calculated parameters are in good agreement with previous work. 31 Cohesive energy was calculated by using the formula given below:…”
Section: Structural Stability and Electronic Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…From our calculations, it is observed that our calculated parameters are in good agreement with previous work. 31 Cohesive energy was calculated by using the formula given below:…”
Section: Structural Stability and Electronic Propertiesmentioning
confidence: 99%
“…S1 (ESI †) shows the obtained phonon dispersion curves, which show good agreement with previous investigations. 31 Most of the BX monolayers are free from imaginary frequencies, except BTe (2H). BTe (2H) can be considered dynamically stable and includes very low imaginary frequencies (À0.224 THz) close to G, due to numerical anomalies that would be improved if a larger supercell or increased k-points were used for calculation.…”
Section: Structural Stability and Electronic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…All 18 MMOs are either semiconductors or insulators, with bandgaps ranging from 1.22 to 6.48 eV, which are comparable to the values of other wide band-gap semiconducting 2D materials, like boron monochalcogenides (with bandgap in the range of 2.06-4.00 eV). 42 In particular, Thus, these MMOs are suitable for potential applications as electronic and optoelectronic devices to operate at much higher voltages, frequencies and temperatures than the conventional semiconductor materials like silicon and gallium arsenide. [43][44][45][46] On the other hand, ZrO 2 and HfO 2 monolayers possess exceptionally large bandgaps of 6.0 and 6.48 eV, and should be considered as 2D insulators.…”
Section: Electronic Structures and Carrier Transport Properties Of Momentioning
confidence: 99%
“…The semiconducting Ibam BH phase transforms into the metallic P6/mmm structure, which also becomes a superconductor with a T c of 14.1 ∼ 21.4 K at 168 GPa [56]. For B-S compounds, most of the current studies are focused on structures and electronic properties at ambient pressure [58][59][60][61][62]. Structural phase transitions of BS and B 2 S 3 have been studied below 50 GPa [63][64][65].…”
Section: Introductionmentioning
confidence: 99%